Optimasi Formula Tablet Salut Enterik Natrium Diklofenak dengan Bahan Penyalut Kollicoat 30 D - Yunarto, Nanang (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2014)
Diclofenac sodium is an analgetic and antiinflammation drug and commonly used by oral administration. Because of it’s side effects that can cause stomach irritation, nausea and vomiting, it’s made in the form of enteric-coated. Enteric-coated formulations developed used organic solvent having toxicity and flammability risks. The aim of this study is to develop diclofenac sodium enteric-coated tablets with a water-based coating material. Coating material used is Kollicoat 30 D which is a derivative of acrylic polymer that can dispersed in water. Optimalization of the formula is done by the weight gain 4%, 6% and 8%. The result showed that enteric coated tablets used coating material with weight gain 8% gave the best result with all parameters meet the requirements of the test, there was no change in acid medium for 2 hours and stable released active ingredient in alkaline medium.